Development of Interactive Videos As a Means of Independent Learning in the Educational Philosophy Course Material Biography and Thinking of Philosophical Leaders - Shadri, Gita Fakhrana; Praherdhiono, Henry; Fajrianto, Ott (Universitas Negeri Malang, 2024)
Students of the class of 2023, Department of Educational Technology, State University of Malang, experienced difficulties in studying the Philosophy of Education course because this course has abstract concepts so it requires additional time to study it. The aim of this research is to develop learning media in the form of interactive videos as a means of independent learning. The course used in this development research is Educational Philosophy, material on the biographies and thoughts of philosophical figures. The media development method uses the Sadiman model (2014) which consists of 9 development stages, namely needs analysis, formulation of learning objectives, formulation of material items, formulation of success measuring tools, media script writing, media production, validation, revision, ready-to-use media. The results of validation development by material experts obtained a percentage of 94.7%, while validation by media experts obtained a percentage of 97.5%. Tests were also carried out on students in measuring media satisfaction, obtaining a percentage of 87.5% and the effectiveness of media obtained a percentage of 96.4%. It can be concluded that interactive video media as a means of independent learning in educational philosophy courses, material on the biographies and thoughts of philosophical figures, has proven to be effective and is included in the valid category and is suitable for use in learning. Keywords: Interactive Videos; Independent Learning; Educational Philosophy